Peningkatan pengetahuan tentang kewirausahaan di pondok pesantren Al Firdaus - Erna Listyaningsih; Dina Dwi Nuryani; Natalina Natalina; Ade Maria Ulfa; Devi Oktarina (JOURNAL of Public Health Concerns, 2025)
Background: One of the challenges faced by Indonesia in global competition is improving the quality of its human resources. The formal and non-formal education sectors also have a very significant role in creating its human resources. Islamic boarding schools are one of the Islamic-based educational communities that have developed quite significantly in Indonesia. Islamic boarding schools as educational institutions have long played a role in shaping the character and knowledge of the young generation in Indonesia. The young generation who have received formal education in Islamic boarding schools should be equipped with expertise or at least have entrepreneurial skills as a form of support in providing a quality generation in the future. A generation that has the ability and has an entrepreneurial spirit will greatly assist in achieving economic growth regionally and nationally. In general, there are still many Islamic boarding schools that have not included an entrepreneurship curriculum in their learning system. Purpose: Providing education about entrepreneurship to students with the aim of improving their abilities to become a generation with an entrepreneurial spirit. Method: This community service activity was held in October 2024 at the Al Firdaus Islamic Boarding School in Kemiling Village, Bandar Lampung City with 89 students with the target of the activity to provide education about the importance of entrepreneurship and its benefits. The education provided is knowledge, insight, understanding, literacy about the basic concepts of entrepreneurship related to managing the environment around the Islamic boarding school such as utilizing organic and inorganic waste into something of economic value. Results: Participants gain knowledge in managing the environment related to waste problems and the participants are also enthusiastic in participating in the activities, listening carefully to the material presented, asking questions and having interactive discussions with the service team during the activity until the end. The participants also get comprehensive solutions about entrepreneurship in addition to managing waste in maintaining environmental health. The implementation of the activity went very well and received a good response in the form of ideas and innovations from the participants. Conclusion: Education to increase knowledge about entrepreneurship can develop the spirit of entrepreneurship, increase literacy, competence, and creativity in the mindset of students. Suggestion: Provide entrepreneurial assistance in Islamic boarding schools to improve the spirit, enthusiasm and entrepreneurial competence of the students of the Al Firdaus Islamic Boarding School so that they will get graduates who have more value, especially knowledge about entrepreneurship and managing environmental health. Keywords: Education; Entrepreneurship; Environmental health; Islamic boarding school Pendahuluan: Salah satu tantangan yang dihadapi Indonesia dalam kompetisi global adalah peningkatan kualitas sumber daya manusianya. Sektor pendidikan formal dan nonformal juga memiliki peranan yang sangat signifikan terhadap penciptaan sumber daya manusianya. Pondok pesantren (Ponpes) adalah salah satu komunitas pendidikan berbasis Islam yang cukup besar perkembangannya di Indonesia. Pondok pesantren sebagai lembaga pendidikan yang telah lama berperan dalam membentuk  karakter  dan  pengetahuan  generasi  muda  di  Indonesia. Generasi muda yang sudah mendapatkan pendidikan formal dikalangan pondok pesantren sebaiknya dilengkapi dengan keahlian atau setidaknya memiliki ketrampilan kewirausahaan sebagai bentuk dukungan dalam penyediaan generasi berkualitas di masa depan. Generasi yang memiliki kemampuan dan memiliki jiwa kewirausahaan akan sangat membantu pencapaian pertumbuhan ekonomi secara regional maupun nasional. Pada umumnya masih banyak pondok pesantren yang belum memasukkan kurikulum kewirausahaan ke dalam sistem pembelajarannya. Tujuan: Memberikan edukasi tentang kewirausahaan pada santri dengan sasaran meningkatkan kemampuan diri menjadi generasi yang memiliki jiwa entrepreneur. Metode: Kegiatan pengabdian kepada masyarakat ini diselenggarakan pada bulan Oktober 2024 di Ponpes Al Firdaus di Kelurahan Kemiling Kota Bandar Lampung dengan jumlah santri sebanyak 89 santri dengan sasaran kegiatan memberikan edukasi tentang pentingnya kewirausahaan dan manfaatnya. Edukasi yang diberikan adalah pengetahuan, wawasan, pemahaman, literasi tentang konsep dasar wirausaha yang berkaitan dengan mengelola lingkungan sekitar ponpes seperti pemanfaatan sampah organik dan anorganik menjadi sesuatu yang bernilai ekonomis. Hasil: Peserta mendapatkan pengetahuan dalam mengelola lingkungan terkait dengan masalah sampah dan para peserta juga antusias mengikuti kegiatan, menyimak dengan baik dari materi yang disampaikan, mengajukan pertanyaan dan diskusi interaktif dengan tim pengabdian selama kegiatan berlangsung sampai akhir. Para peserta juga mendapatkan solusi komprehensif tentang kewirausahaan selain dari mengelola sampah dalam menjaga kesehatan lingkungan. Pelaksanaan kegiatan berjalan dengan sangat baik dan mendapatkan respon baik berupa munculnya ide dan inovasi dari para peserta. Simpulan: Edukasi peningkatan pengetahuan tentang kewirausahaan dapat mengembangkan semangat jiwa wirausaha, meningkatkan literasi, kompetensi, kreativitas pola pikir para santri. Saran: Memberikan pendampingan kewirausahaan di pondok pesantren  untuk  meningkatkan  jiwa,  semangat  dan  kompetensi  kewirausahaan  para santri Pondok Pesantren Al Firdaus  sehingga  akan mendapatkan lulusan santri yang memiliki  nilai lebih terutama pengetahuan tentang kewirausahaan dan mengelola kesehatan lingkungan.